Development and characterization of functional O/W emulsions with chia seed (Salvia hispanica L.) by-products - Julio, Luciana Magdalena (2016)
The present work investigated the physicochemical properties of O/W emulsions containing functional ingredients (oil with high x-3 fatty acid content, protein and/or soluble fiber) from chia seeds. The effect of different protein–carbohydrate combinations (sodium caseinate and lactose, sodium caseinate and maltodextrin, chia protein-rich fraction and maltodextrin) and the presence of chia mucilage (0 and 0.2 % wt/wt) in the aqueous phase of chia O/W emulsions was studied as a function of droplet size distribution, Sauter mean diameter, f-potential, rheological properties and backscattering profiles. The use of sodium caseinate in combination with lactose or maltodextrin produced chia O/W emulsions with small droplet size (0.22–0.27 lm), high degree of uniformity in droplet size distribution, negatively charged droplets (at pH 6.5), pseudoplastic behavior and high physical stability. Emulsions with chia protein-rich fraction presented wider droplet size distribution and higher D[3,2] values than the previous ones, recording a Newtonian behavior. The addition of chia mucilage affected the physicochemical properties studied, mainly the rheological characteristics of emulsions.